Radiotherapy for node-positive prostate cancer: 2019 Recommendations of the Australian and New Zealand Radiation Oncology Genito-Urinary group. (November 2019) - Lieng, Hester; Kneebone, Andrew; Hayden, Amy J.; Christie, David R.H.; Davis, Brian J.; Eade, Thomas N.; Emmett, Louise; Holt, Tanya; Hruby, George; Pryor, David; Sidhom, Mark; Skala, Marketa; et al.
Abstract: The management of node-positive prostate cancer is highly variable, with both locoregional and systemic treatment options available. With the increasing use of novel imaging techniques such as PSMA-PET and MRI, combined with the increasing use of surgery for high-risk prostate cancer, clinical and pathological regional nodal disease is being detected at a higher rate and at an earlier stage than previously. This creates a window for a potentially curative management approach. The role of radiotherapy including optimal radiation target volumes and dose, as well as the timing and duration of accompanying systemic therapy remains uncertain. At a workshop in 2017, the Australian and New Zealand Faculty of Radiation Oncology Genito-Urinary Group (FROGG) identified variations in the management of node-positive prostate cancer identified on primary staging or on histopathology at radical prostatectomy. FROGG reviewed the literature and developed a set of evidence-based recommendations on the appropriate investigation and management of clinically and pathologically node-positive prostate cancer. These recommendations encompass imaging techniques, radiation treatment target volumes and doses, as well as the use of androgen deprivation therapy.